Post-komunistične stranke - primerjava razvoja Zveze komunistov Slovenije in Komunistične stranke Češkoslovaške - Balut, Aleš (Teorija in praksa, 2000)
The article presents a brief comparison of the development of communist parties in present day Czechoslovakia and Slovenia, starting with a view into the past focused especially on activities during the liberation from nazism, ie. fachism in 1945 up till present day. The more significant part of our analysis focuses on the development of both parties from the independence of Slovenia on one hand, and the so-called velvet revolution and separation of Czechoslovakia on the other. The parties have, due to their different socio-economic and political conditions and tendencies, each followed their separate routes. The most significant conclusion of the comparison is certainly the fact that ZLSD has transformed into a modern social democratic party that is potent with the pragmatism of the younger generation and her politicians, and therefore has, compared to KSČM, great coalition potential. Contrary to this, KSČM was not, and is not able to transform from the outlived, conservative political party controlled by the old communist elite, into a modern social democratic party. For this reason KSČM remains isolated in the political arena, or put differently, has a relatively low coalition potential.
Keywords: political party; politične stranke; Czech Republic; Češka; Slovenia; Slovenija; tranzicija; politična levica; postkomunizem